ETHICS IN PASTORAL MINISTRY - Kanniyakonil, Scaria (Asian Horizons, 2020)
The role of the pastor is to help the faithful to make communion with God. In order to attain this goal, a pastor proclaims the word of God and celebrates the sacraments, and he also needs a good relationship with people. The Catholic Church has a deep theological and practical vision for pastoral ministry. However, during the course of the pastoral ministry, the pastor faces many moral issues. Consequently, there arises problems related to relationship, confidentiality, use of finance, respecting others, organization of church institutions, and execution of power. We propose Christian care ethics in pastoral ministry where Jesus Christ is the model who touched people psychically, emotionally, intellectually, and spiritually at a deep level. This may help to provide the best approach in the pastoral ministry. Moreover, continual spiritual formation is necessary that directs and empowers an ethical pastoral life. Similarly, theological and psychological competence may support the pastor to form an excellent pastoral ministry.